Resilience and the Re-integration of Street Children and Youth in Sub-Saharan Africa The Case of Cameroon - Sanji, Walters Mudoh (SpringerBriefs in Psychology,, 2018)
This book contributes to a better understanding of street children and youth within Sub-Saharan Africa. It investigates the psychological conditions of these children and determines how to reintegrate them into mainstream socio-economic activities. The book proposes cures and preventive measures. It also highlights the inextricable link which exists between street children and youth problem, and economic underdevelopment within Sub-Saharan Africa. With a careful examination of the main reasons of poverty and weak institutions within the region, the book offers suggestions on how to prevent street children and youth problem by alleviating poverty through a vibrant industrial sector and economic development. This book also provides recommendations on how to cure the problem by creating social enterprises which can offer opportunities to the youth and their parents. It achieves this by first comparing children and youth on the street (those who have homes to return to at night), with children and youth of the street (those who both work and live on the street). It then looks at a project designed to boost the resilience of street children. By looking at the differences between children on the street and children of the street, the book highlights the importance of having a home, and of the great value of cooperation between churches, non-government organizations and the state, in working to make the lives of these young people better. This book is a useful resource for students, academics and researchers in the fields of psychology, social work, sociology, and international development.